1999
DOI: 10.2337/diacare.22.1.50
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, immunological, and genetic heterogeneity of diabetes in an Italian population-based cohort of lean newly diagnosed patients aged 30-54 years. Piedmont Study Group for Diabetes Epidemiology.

Abstract: Almost 50% of lean young and middle-aged patients were ICA+ and/or anti-GAD+, suggesting a high prevalence of a slowly evolving form of type 1 diabetes. The evaluation at diagnosis of both beta-cell secretory capacity and markers of autoimmunity is recommended to provide a pathogenetic classification of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
19
0
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 0 publications
3
19
0
1
Order By: Relevance
“…Unfortunately, only few large studies have characterised antibody-positive diabetes in both young and middle-aged patients [11,14,15]. Also, to date, diagnosis of type 2 diabetes has been by exclusion, with patients not presenting with genetic and autoimmune markers of type 1 diabetes being considered to have type 2 diabetes [3,11,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, only few large studies have characterised antibody-positive diabetes in both young and middle-aged patients [11,14,15]. Also, to date, diagnosis of type 2 diabetes has been by exclusion, with patients not presenting with genetic and autoimmune markers of type 1 diabetes being considered to have type 2 diabetes [3,11,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Another Swedish study (32) reported that the prevalence of GAD antibodies was 8% overall in newly diagnosed diabetic patients and only 3.2% in patients classified as having type 2 diabetes. A Dutch population-based study (33) found GAD antibody positivity in 3.5% (95% CI 0.7-10%) of patients already known to have diabetes (type 1 or type 2), whereas, although different criteria were used, a higher prevalence of GAD positivity (Ͼ20%) was observed in Northern Italy (34). In the U.K.…”
Section: Immune Markersmentioning
confidence: 99%
“…The proportion of LADA among those patients attending diabetes clinics has been investigated in two previous studies in Italy; one performed in a subset of lean diabetic patients (13) and the other at a single institution (14).…”
Section: Introductionmentioning
confidence: 99%